PERCEPTUAL LEARNING STYLE PREFERENCES OF ENGLISH DEPARTMENT STUDENTS AT UNIVERSITAS RIAU - Soraya, Tifanny; Erni, Erni; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The method each student chooses to pay attention to, receive, andretain new information is known as learning style. The student's learning style is one ofthe aspects that will influence the student's performance in learning activities. Thepurpose of this study is to ascertain the learning style preferences of EnglishDepartment students at Universitas Riau. The participants in this study were fortyEnglish Study Program four-semester students. The research data was collected usingReid's (1987) Perceptual Learning Style Preferences (PLSP). Descriptive statistics wereused to analyze the quantitative data, which was collected using Perceptual LearningStyle Preferences Questionnaire (PLSPQ). The results showed that the four- semesterEnglish Study Program students of FKIP Universitas Riau had a variety of learningstyles, with visual, auditory and individual learning style being the preferred followedwith tactile, kinesthetic and group learning style being the least preferred.Key Words: Learning Style, Perceptual Learning Style Preferences, English Students.